Pengaruh Penerapan Standar Akuntansi Pemerintah, Kompetensi Sumber Daya Manusia, Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Badan Pengembangan Sumber Daya Manusia Provinsi Sulawesi Selatan - Andi Tenri Ellyanti Entong; Dr Mursalim; Dr Ibrahim Dani (Tangible Journal, 2018)
This research was conducted with the aim to: (1) the influences of aplications of Government Accounting Standard to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province; (2) the influences of Human Resource Competence to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province; and (3) the influences of the use of Information Technology to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province. This research use a scientific approach. This rsearch use 37 employeees as respondents with their main duties and functionin carrying out their works. The research result showed that: (1) the application of Government Accounting Standard had influential but not significant to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province; (2) the Human Resource Competence had influential and significant to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province; and (3) the use of Information Technology had influential but not significant to The Quality of Financial Report in Human Resource Development Agency Sulawesi Selatan Province.